The Role of Genetics in Dark Triad Personality Traits - Temelli, Ecenur; Kaya, Sibel; Kazgan, Mukaddes Hayal; Yılmaz, Nazire Ayşenur; Ayar, Emre; Yükseloğlu, Emel Hülya (The Bulletin of Legal Medicine, 2021)
Objective: Dark Triad is an umbrella term that involves sub-clinical psychopathy, narcissism and Machiavellianism. According to the researches studied the related factors about the development of Dark Triad, there may be a relationship within the environmental, biological and genetic factors and dark triad personality traits. The aim of this study is, examining both Dark Triad personality traits and the researches about the role of genetic in the development of Dark Triad’s three types. Methods: In this direction, this research examines family, twin and candidate gene studies about the hereditary components of Dark Triad, narcissism, psychopathy and Machiavellianism. Also, researches examining the genetic components of some personality traits known to be related to the Dark Triad are included. Conclusion: It’s seen that, all three sub-personality types are affected by genetic factors, the hereditary characteristics of psychopathy and narcissism are more than Machiavellianism, among the three personality types, the personality type that is most affected by environmental factors is Machiavellianism and the personality traits related to the Dark Triad can also be determined by some genetic factors according to reviewed studies.